Optical and luminescence properties of Er,Yb:YAG crystals grown by horizontal directional crystallization method - Nizhankovskyi, S.V.; Kozlovskyi, A.A.; Kovalenko, N.O.; Vovk, O.O. (Functional Materials, 2019)
The spectral properties of Er,Yb co-doped Y₃Al₅O₁₂ single-crystals grown for the first time by modified horizontal directional crystallization method in reducing atmosphere Ar+(CO, H₂) are reported in the paper. Optical absorption and photoluminescence spectra indicated that doping ions are effectively incorporated into the garnet crystal matrix. Photoluminescence spectra were measured under the 920 nm excitation. The strongest IR emission peaks were located at 1531 nm and 1619 nm. The up-conversion red and green emission lines were also recorded.